Evaluation of the curriculum of Islamic education for the secondary school system decisions in the Kingdom of Saudi Arabia in the light of the principles of human rights - Al-Omari, Mohammed Ali Ahmed; Ali, Amal Mahmoud (Journal of Educational and Psychological Sciences, 2019)
The study aims to identify the contents of the books of Islamic education in general education in the Kingdom of Saudi Arabia and the principles of human rights. The report on the amount of Islamic education curricula for the secondary stage must be available in the curricula of Islamic education curricula at the secondary level. . Study Methodology: Analytical Descriptive Method The most important results of the study were human rights in Islamic education curricula (782) times. It is clear that the rate of reproduction (7. 9%) at the latest. (38. 36%), political rights (28. 52%), economic rights (19. 44%) and educational rights (19. 44%). (13. 68%). In the category of Quranic verse (13. 94%), in the category of Quranic verse (13. 94%), Hadith of the Prophet in the last corner by (7. 54%). One of the most important ways in which the actors and the parties to the Middle East Peace Treaty are concerned is by the Supreme Court. And taking into account the balance of human rights revenues in education curricula.